Protocol for a systematic review of living labs in agricultural-related systems - Maryam Yousefi; Frank Ewert (Sustainable Earth Reviews)
Abstract Background Living labs are innovative platforms that bring together stakeholders (academic and non-academic actors from diverse disciplines), to collaboratively co-create, develop and test new technologies, products, services in real-life environments. As living labs become increasingly popular in addressing sustainability challenges in agriculture, it is essential to understand the potential of living labs to support innovation in the agricultural context. However, the existing knowledge is dispersed, and uncertainties remained regarding their approaches, methods, and outcomes. To address this gap, this study outlines a systematic review protocol of the existing literature on living labs in agricultural-related contexts. This will be done through questions focusing on the contributions of living labs to agricultural sustainability and innovation, their effectiveness, and strategies for development and implementation. Additionally, it will identify areas that require further research and development to advance our understanding of these initiatives. Method This study will be conducted according to the RepOrting Standards for Systematic Evidence Syntheses (ROSES) review protocol. We will search databases, including Scopus, Web of Science (core collection) and Google Scholar, which will be limited to titles, abstracts, and keywords in English to eliminate irrelevant literature. The quality of the method used for each selected study will be evaluated using the Critical Appraisal Skills Program, Qualitative Research Checklist. Coding and data extraction will include for example bibliographic information, types of agricultural practices tested, dominant framework (e.g. open innovation, user innovation, and participatory design), the contribution of living lab in agriculture, stakeholder roles, etc. We will use thematic analysis to synthesise our findings. We will compare descriptive and narrative sub-groups to take into account differences in living lab concepts in relation to the context, outcomes, and limitations. Conclusions The results of this review will provide a foundation for informing user-centred innovations in agriculture using living lab methodology. Researchers and practitioners working in areas such as co-design which incorporate user involvement, collaboration, and knowledge exchange, may also benefit from these findings.